IL7 and IL7 Flt3L co-expressing CAR T cells improve therapeutic efficacy in mouse EGFRvIII heterogeneous glioblastoma - Swan, Sheridan L.; Mehta, Nalini; Ilich, Ekaterina; Shen, Steven H.; Wilkinson, Daniel S.; Anderson, Alexa R.; Segura, Tatiana; Sanchez-Perez, Luis; Sampson, John H.; Bellamkonda, Ravi V. (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR) T cell therapy in glioblastoma faces many challenges including insufficient CAR T cell retention and antigen-negative tumor cells evading targeting. Unfortunately, preclinical studies evaluating CAR T cells in glioblastoma focus on tumor models that express a single antigen, use immunocompromised animals, and/or pre-treat with lymphodepleting agents. While lymphodepletion enhances CAR T cell efficacy, it diminishes the endogenous immune system, which has the potential for tumor eradication. Here, we delivered IL7 and/or Flt3L expressing CAR T cells in 50% EGFRvIII-positive and -negative orthotopic tumors pre-conditioned with non-lymphodepleting total body irradiation. IL7 and IL7 Flt3L CAR T cells increased intratumoral CAR T cell abundance seven days after treatment. IL7 co-expression with Flt3L increased conventional dendritic cells as well as the CD103+XCR1+ population known to have migratory and antigen cross-presenting capabilities. Treatment with IL7 or IL7 Flt3L CAR T cells improved overall survival to 67% and 50%, respectively, compared to 9% in vCAR and vFL and no survivors in the PBS control. We conclude that CAR T cells modified to express IL7 enhanced CAR T cell abundance and eliminated EGFRvIII heterogeneous tumors pre-conditioned with non-lymphodepleting irradiation.